Fourier Transform to Solve Infinite String Free Vibration of Application - Li, Xiaofeng; Dong, Xiaoxu; Zhang, Lihua (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2016)
This paper presents the definite solution of equations of infinite string free vibration problem and the establishment of conditions, given the definite solution to solve the problem of two algorithms based on Fourier transform for solving partial differential equations are general steps. The problem solving differential equations after some converted into solving the problems of ordinary differential equations, and then to ask as a function of quadrature or inverse solution to give the original solution to the problem.